2022
DOI: 10.1021/acs.iecr.2c02731
|View full text |Cite
|
Sign up to set email alerts
|

Porosification and Fe3+ Intercalation of Spent LiCoO2 as an Efficient Oxygen Evolution Electrocatalyst

Abstract: Lots of spent Li-ion batteries have caused waste of mineral resources and environmental pollution. However, it is extremely challenging to develop more efficient recycling methods. Therefore, in this paper, the reconstitution of spent lithium cobalt oxides (LiCoO2) was achieved by delithiation and iron intercalation in an aqueous two-electrode system, which was used for the oxygen evolution reaction. The electrochemical deintercalation of Li+ promoted the formation of 3D porous LiCoO2, which exposed more activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, by controlling the delithiation time, half of the lithium is still used to maintain the original layered structure, which contributes more favorable conditions for the OER. 25 The DLSLCO was further heat-treated with Ar/H 2 at different temperatures. The XRD patterns of heat-treated samples are displayed in Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by controlling the delithiation time, half of the lithium is still used to maintain the original layered structure, which contributes more favorable conditions for the OER. 25 The DLSLCO was further heat-treated with Ar/H 2 at different temperatures. The XRD patterns of heat-treated samples are displayed in Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is due to the fact that the closely stacked layers of LiCoO 2 are destroyed after delithiation. However, by controlling the delithiation time, half of the lithium is still used to maintain the original layered structure, which contributes more favorable conditions for the OER …”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al demonstrated the Co 3 O 4 phase formed on the surface (Figure 4a) of LCO during cycling at the atomic level by transmission electron microscopy (TEM), [66] which is con-firmed by the XRD and Raman results. Li and Wang et al found that there were obvious cracks and holes on the surface and inside (Figure 4b,c) of the spent LCO, [65,67] which formed due to stress concentration during cycling. The formation of Li vacancies in LCO is accompanied by vigorous Li + deintercalation and The XRD patterns of spent LCO and regenerated LCO with different regenerated conditions.…”
Section: Degradation Mechanisms Of Lco and Corresponding Characteriza...mentioning
confidence: 99%
“…Li and Wang et al. found that there were obvious cracks and holes on the surface and inside (Figure 4b,c) of the spent LCO, [ 65,67 ] which formed due to stress concentration during cycling. The formation of Li vacancies in LCO is accompanied by vigorous Li + deintercalation and intercalation, causing uneven stress distribution in the LCO lattice structure, was proved by continuous changes of diffraction peak around 19° in the XRD pattern upon cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation